The Effect of Organizational Learning and Innovation on Business Performance of SMEs of Rattan Product Manufacturing in Cirebon Regency, West Java Province, Indonesia - Indra Muis (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2014)
Abstract: This research is to find out the effect of organizational learning and innovation on business performance of Small-Medium Enterprises (SMEs) manufacturing rattan products in West Java Province, Indonesia. After understanding literatures on organizational learning, innovation, and business performance. the research then formulates a model of organizational learning, innovation and business performance and defines how those variables are associated. Hypotheses on organizational learning - business performance, innovation-business performance. and learning organization-innovation association are tested. Organizational learning is measured based on 4 (four) dimensions. namely: information acquisition, information distribution, information interpretation, and behavioral and cognitive changes. Innovation is measured based on 3 (three) dimensions, namely: product and service innovation. process innovation, and innovative culture. Business performance is measured based on financial and non-financial performance of the enterprises. Validity and reliability tests are conducted by using SPSS 21. Then, the association is tested through Structural Equation Modeling (SEM) from a database of 109 SMEs in rattan product manufacturing in Cirebon Regency, West Java Province. The results show that the presence of organizational learning and innovation is associated to business performance of SMEs as stated in the proposed model. Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh pembelajaran dan inovasi organisasi terhadap kinerja usaha produk rotan industri kecil menengah di Jawa Barat, Indonesia. Setelah memahami literatur tentang pembelajaran organisasi, inovasi, dan kinerja bisnis. penelitian kemudian merumuskan model pembelajaran organisasi, inovasi dan kinerja bisnis dan menentukan bagaimana variabel tersebut terkait. Hipotesis tentang pembelajaran organisasi - kinerja bisnis, inovasi-kinerja bisnis. dan asosiasi organisasi-inovasi pembelajaran diuji. Pembelajaran organisasional diukur berdasarkan 4 (empat) dimensi. yaitu: perolehan informasi, distribusi informasi, interpretasi informasi, dan perubahan perilaku dan kognitif. Inovasi diukur berdasarkan 3 (tiga) dimensi, yaitu: inovasi produk dan layanan. inovasi proses, dan budaya inovatif. Kinerja bisnis diukur berdasarkan kinerja keuangan dan non keuangan perusahaan. Uji validitas dan reliabilitas dilakukan dengan menggunakan SPSS 21. Kemudian, asosiasi diuji melalui Structural Equation Modelling (SEM) dari database 109 UKM dalam pembuatan produk rotan di Kabupaten Cirebon, Provinsi Jawa Barat. Hasil penelitian menunjukkan bahwa kehadiran pembelajaran dan inovasi organisasi dikaitkan dengan kinerja bisnis UKM sebagaimana tercantum dalam model yang diusulkan.